Формування маркетингової стратегії туристичних підприємств - Шквиря, Наталя Олександрівна; Шквыря, Наталья Александровна; Shkvyria, Natalia (Мелітополь: ТДАТУ, 2014)
UK: Проаналізовано результати діяльності туристичних фірм України. Визначено алгоритм формування маркетингової стратегії туристичних підприємств. Розроблено методичні підходи до вибору маркетингової стратегії розвитку туристичних підприємств на основі їх конкурентної позиці на ринку послуг. EN: Problems of tourism development at the present stage management are important objects of theoretical and applied research. Tourism is one of the most important factors of the areas socio-cultural development, increase the level and quality of life. The activity of Ukraine tourism enterprises is analyzed. It is proved that the basis of tourism enterprise market is a marketing strategy that helps optimize the internal environment and provides advantages in competition. Proved that the basis for choosing a marketing strategy for tourism enterprises should act level of competitiveness. To implement our statement was developed and tested the algorithm of marketing strategy choice for tourism enterprises in the market on the basis of its competitiveness. It includes an assessment of tourism services for the quality, for pricing and for marketing tools. To assess the competitiveness of the tourism enterprise service quality were chosen following indicators: indicators characterizing the services range; reliability; safety performance; spatial indices; performance of professional staff; information indicators. The indexes that characterize the compliance of tourism enterprises market requirements are proposed. Competitiveness leading travel companies Ukraine on the proposed method is estimated. The results of determining competitive advantage, competitive position and competitiveness of tourism enterprises can be used when selecting a marketing strategy for the development of the tourism market.
Keywords: туристичне підприємство; туристичні послуги; маркетинг; стратегічний маркетинг; маркетингова стратегія; конкурентні переваги; конкурентоспроможність підприємства; tourism enterprises; tourist services; marketing; strategic marketing; marketing strategy; competitive advantages; enterprise competitiveness